Time will tell: Temporalities of a European land deal in Zambia and its critics. Issue 137 (December 2022) - Salverda, Tijo
Abstract: Like many other examples of the ongoing global land rush, a large Zambian land deal initiated by a European agribusiness in 2012 was met with cries of alarm from international critics about the amount of land purchased and the negative impact the investment could have on local residents. The agribusiness, however, responded relatively quickly. Not only did this initially contribute to protecting the position of (affected) residents, but it also enhanced the image of the agribusiness as a corporation willing to listen to concerns. As with land deals elsewhere, though, the situation looks much different ten years on, with the project not living up to its promises, either financially or regarding rural residents. To better understand these discrepancies, a closer look at various temporalities together is revealing – importantly, as others have discussed, because tensions between temporal dimensions of finance and agriculture frequently affect land deals. But simultaneously, as the Zambian case demonstrates, (international) critics, such as advocacy groups, NGOs, and media, operate according to particular temporal dynamics – with attention devoted to the investment fluctuating over time – while (local) stakeholders, including neighbouring rural residents and state institutions refraining from enforcing the agribusiness to honour agreements along the line, also affect developments. Through analysing these temporalities over an extended period of time, this article aims to contribute to an understanding of challenges involved in holding land deals to account. Accordingly, broader lessons can be drawn about the ambiguous potential for mitigating negative effects of large-scale land acquisitions – and corporate practices more generally.